Factors Contributing to the Performance of Farmer Producer Organizations (FPOs) – a Study in Medak District of Telangana State - C. D, Amitha; B., Savitha.; V., Sudha Rani.; P., Laxminarayana (International Journal of Bio-resource and Stress Management, 2021)
A study was conducted on the performance of FPOs and the factors contributing to performance of FPOs in Medak district of Telangana State, India. Three FPOs were selected randomly from 3 different promoting institutes viz., Suraksha Farmers Producer Company Ltd (SFPCL) promoted by independent research organization Centre for Sustainable Agriculture (CSA), Marpalli Kisan Kranthi Producer Company Ltd (MKKPCL) promoted by Vrutti NGO and Siddipet Kisan Agro Farmers Producer Company Ltd (SKAFPCL) promoted by International Crops Research Institute for the Semi-arid Tropics (ICRISAT). The Ex-post facto research design was adopted for the study with a sample of 90 producer members, covering three FPOs in erstwhile Medak district of Telangana State. From the analysis, it was found that overall performance of FPOs in Medak district was average to poor. The factors viz., education, group leadership, group communication, adherence to rules, group participation, and team spirit had showed positive and significant relationship with performance. The results of regression analysis inferred that all the selected twelve factors put together explained the variation to the extent of 72.47% in the performance of the FPO with leadership of officials and participation of members contributing significantly to the performance of FPOs.